Die beschäftigungspolitischen Konsequenzen von „Rot-Grün“ - Heine, Michael; Herr, Hansjörg (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 1999)
With mass unemployment in Germany and elsewhere showing no signs of abating, numerous economists and politicians of the neo-classic school have become vocal in calling for the flexibilization of the labour market. A demand for wage cuts forms the nub of their solution to the crises. The article shows that such approaches are both theoretically flawed and unable in practical terms to deliver what they promise, as cuts in wages will not lead th higher levels of employment but will rather increase the danger of a deflationary spiral. An alternative monetary-Keynesian model is proposed as a basis for more suitable labour market policymaking.